Early Exposure and Its Impact on Cardiothoracic Surgery: an Experience of Medical Education in The United Kingdom - Jeremy Chan (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2022)
Introduction: Cardiothoracic surgery (CTS) has seen a decline in interest and application rates in recent years. As a relatively small speciality, teaching and placements in CTS are often not included during undergraduate study and postgraduate training. We aim to evaluate the exposure to CTS during both undergraduate study and postgraduate training. Methods: A ten-question online survey was designed and delivered to Foundation Year Two (FY2) doctors who graduated in 2017 and completed their two-year postgraduate foundation training in 2019. Medical schools with no graduates in 2017 and 2018 were excluded from our study. IBM® SPSS Statistics, version 25, and Microsoft Excel 365® were used for Student’s t-test statistical analysis. Results: Three hundred and six FY2 doctors across 16 medical schools completed the survey, none of which included compulsory CTS attachments as their undergraduate curriculum. Thirty-two respondents (10.5%) underwent CTS attachments lasting between one to three weeks. Only 14 (43.8%) had worked in a cardiothoracic unit during their two-year Foundation Programme; 10 of which (71.2%) subsequently made an application for cardiothoracic speciality training. Most of the participants with previous exposure to CTS, during either undergraduate study or postgraduate Foundation Programme training or both, were significantly more likely to make an application to CTS training (P<0.05). Conclusion: Our study suggests that doctors with increased exposure to CTS during undergraduate study and postgraduate training are more likely to pursue a career in CTS. Targeted interventions at both stages may improve interests in CTS and the number of prospective applicants.